RARE GAS ISOTOPES AND PARENT TRACE ELEMENTS IN ULTRABASIC-ALKALINE-CARBONATITE COMPLEXES, KOLA PENINSULA: IDENTIFICATION OF LOWER MANTLE PLUME COMPONENT - Tolstikhin I.N.; Kamensky I.L.; Nivin V.A.; Vetrin V.R.; Balaganskaya E.G.; Ikorsky S.V.; Gannibal M.A.; Marty B.; Weiss D.; Verhulst A.; Demaiffe D. (My University, 2002)
During the Devonian magmatism (370 Ma ago) ∼20 ultrabasic-alkaline-carbonatite complexes (UACC) were formed in the Kola Peninsula (north-east of the Baltic Shield). In order to understand mantle and crust sources and processes having set these complexes, rare gases were studied in ∼300 rocks and mineral separates from 9 UACC, and concentrations of parent Li, K, U, and Th were measured in ∼70 samples. 4He/3He ratios in He released by fusion vary from pure radiogenic values ∼108 down to 6 × 104. The cosmogenic and extraterrestrial sources as well as the radiogenic production are unable to account for the extremely high abundances of 3He, up to 4 × 10−9 cc/g, indicating a mantle-derived fluid in the Kola rocks. In some samples helium extracted by crushing shows quite low 4He/3He = 3 × 104, well below the mean ratio in mid ocean ridge basalts (MORB), (8.9 ± 1.0) × 104, indicating the contribution of 3He-rich plume component. Magnetites are principal carriers of this component. Trapped 3He is extracted from these minerals at high temperatures 1100°C to 1600°C which may correspond to decrepitation or annealing primary fluid inclusions, whereas radiogenic 4He is manly released at a temperature range of 500°C to 1200°C, probably corresponding to activation of 4He sites degraded by U, Th decay.